2017
DOI: 10.1159/000477726
|View full text |Cite
|
Sign up to set email alerts
|

The Trend of Change of Allergic Diseases over the Years: Three Repeated Surveys from 1994 to 2014

Abstract: Background: Although it is known that there has been an increase in asthma and allergic diseases among school-aged children, results vary between countries. The aim of this study was to examine trends in the prevalence of these diseases in the city of Adana (south Turkey) over the last 20 years based on the results of 3 cross-sectional studies. Methods: Three cross-sectional surveys were performed 10 years apart in south Turkey. Here, we compare the surveys conducted among children between the ages of 6 and 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 20 publications
0
16
1
Order By: Relevance
“…Since diseases are strongly affected by the environment which typically changes over time, the temporal trend of a disease can exhibit a distinct direction. Indeed, cardiovascular diseases, diabetes mellitus, cancer, infectious diseases, and allergic diseases have shown an apparent upward or downward trend in recent decades 1621 . Conversely, although social distress such as natural disasters and economic crises impact upon psychological distress and depression 2224 , most recent research has reported little to no change in the prevalence of psychological distress over recent decades, with the exception of a Taiwanese study 6,7,911,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Since diseases are strongly affected by the environment which typically changes over time, the temporal trend of a disease can exhibit a distinct direction. Indeed, cardiovascular diseases, diabetes mellitus, cancer, infectious diseases, and allergic diseases have shown an apparent upward or downward trend in recent decades 1621 . Conversely, although social distress such as natural disasters and economic crises impact upon psychological distress and depression 2224 , most recent research has reported little to no change in the prevalence of psychological distress over recent decades, with the exception of a Taiwanese study 6,7,911,14 .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Since no effective methods are currently available to prevent allergic rhinitis either in children or adults, its prevalence has increased in recent years. 4,5 Allergic rhinitis is often accompanied by various health problems, including asthma, atopic dermatitis, or allergic conjunctivitis. Although sleep disorders, productivity loss, attention deficits, and learning difficulties are observed in allergic rhinitis cases, 6 they have received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Since no effective methods are currently available to prevent allergic rhinitis either in children or adults, its prevalence has increased in recent years. 4,5…”
Section: Introductionmentioning
confidence: 99%
“…Atopic diseases are among the most common chronic diseases in children and adolescents, and an increasing prevalence has been observed over several decades . Due to the cohort effect, this increase should now appear in adulthood.…”
Section: Introductionmentioning
confidence: 99%